Evaluation of the anti-inflammatory effect of the aqueous extract of the seeds of lupinus mutabilis sweet (tarwi, chocho), in experimental animals - Castañeda, C. B. (2022)
In the investigation carried out in the seed of Lupinus mutabilis Sweet it has been possible to identify by means of a Screening Phitochemistry the present biologically active principIes in the watery extract in boiled, being determined the total alkaloids.The acute toxicity has been evaluated (LD50) so much of the watery extract as of the obtained total alkaloids of the seed.In the watery extract of the seeds the activity antiinflammatory has been evidenced (acute and subchronicle) in experimental models, being administered the Lupinus for oral route to a dose of 2000 mg/Kg of weight. The inflammation was evaluated by different techniques using the technique of Granuloma of Pouche with trementin in rats (Inflammation sub-chronicle) and inflammatory to plant with formol to 1 % and ovoalbúmina to 50% in S.S.I. in mice, following the standard techniques of the CYTED, being obtained the maximum effect of inhibition from the inflammation to the 80 minutes in comparation with the 60 minutes corresponding to the dic10fenac (30 mg/Kg) showing a percentage of inhibition of 66% in front of 100% of the standard drug. The LD50 of the watery extract in boiled for oral route it was of 3500 mg/Kg of weight and of the complete alkaloids administered for oral route it was of 600 mg/Kg.The alkaloids have been identified by TLC (Thin layer chromatography) and HPLC comparing it with standard of Spartein.